The influence of roads on the species diversity of forest vascular flora in Central Poland - Zielińska, Katarzyna (Biodiversity: Research and Conservation, 2007)
The influence of the presence of roads on the diversity and degree of vascular flora synanthropization of Querco-Pinetum phytocoenoses was the focus of the investigation. The role of road category was evaluated taking into account forest tracks, admitted only for forest administration, dirt roads admitted to traffic and tarmac roads. The research was carried out in the forests of BolimUw Landscape Park in the years 2000-2003. The linear transect method was applied. There were 105 transects, each comprised three research plots lying in various distances from the road. For each investigated plot a list of species together with their cover measure was made. The significant influence of the presence of roads on the species diversity of the vascular flora of forest communities was proved. The increase in diversity of the areas located close to transport routes was an effect of greater richness, composed of locally rare species and to a lesser extent was the result of increase in variety of taxonomic and ecological features of species. The presence of roads was the cause of the simultaneous increase in the extent of synanthropization. It was observed that the road category is of significance to the degree of influence on the composition of forest flora. The most exploited roads contributed to the biggest changes in flora composition.